AB0193 Inhibitory Effect of 1, 25OH Vitamin D on IL-17 Related Pro-Fibrotic Cytokines Expression in Peripheral Blood Mononuclear Cells of Patients with Systemic Sclerosis. (9th June 2015) - Corrado, A.; Mele, A.; Colia, R.; Marucci, A.; Cantatore, F.P.
Abstract : Background: The role of IL17 cells in the pathogenesis of Systemic Sclerosis (SSc) has recently emerged, as it has been reported that IL-17 is overproduced by T cells from the peripheral blood and fibrotic lesions of the skin and lungs in SSc patients and it is able to enhance the proliferation of fibroblasts in vitro . In the latest years also the anti-inflammatory, anti-apoptotic, and anti-fibrotic effects of Vitamin D have gained considerable attention and it has been hypothesized that Vitamin D could have a modulating effect on SSc. Objectives: The aim of this study is to examine the in vitro expression of IL-17 and pro-fibrotic cytokines in peripheral blood mononuclear cells (PBMCs) from subjects with SSc and to evaluate the effects of IL-17 neutralizating antibodies and 25OH Vitamin D on the expression of these cytokines. Methods: PBMCs were isolated from 16 subjects fulfilling the 2013 ACR/EULAR criteria for SSc (16 women, mean age 51, 3±6, 7 years, range: 42-65); 10 matched healthy subjects (10 women, age 48, 9±8, 1 years, range: 41-61) was used as control. Secretion of IL-17 and pro-fibrotic cytokines (TGFβ, CTGF and PDGF) was detected by ELISA in PBMCs of both SSc and control group; the expression of specific mRNA for these cytokines was confirmed by RT-PCR analysis. To confirm the relationship between IL-17 and the expression of pro-fibrotic cytokines and to evaluate the possible anti-fibrotic effect of Vitamin D, the secretion and the expression of the pro-fibrotic cytokines were assessed in PBMCs from SSc after treatment with IL17 neutralizing antibodies or increasing concentrations (10 -10 to 10 -6 M) of 1, 25(OH)2 D3 . Results: The expression of IL17, TGFβ, CTGF and PDGF was significantly higher in PBMCs from SSc subjects compared to healthy controls. Neutralization of IL-17 in the culture medium of SSc PBMCs decreased mRNA expression and protein secretion of TGFβ, CTGF and PDGF. The addition of Vitamin D in SSc PBMCs significantly reduced the expression of pro-fibrotic cytokines compared to untreated cells only at higher concentration (10 -6 M); with the same concentration of Vitamin D a slightly reduction of IL-17 production compared to untreated cells was observed, which did not reach statistical significance. Nevertheless, the inhibition of pro-fibrotic cytokines production induced by the higher concentration of Vitamin D was significantly lower compared to the inhibition induced by IL-17 neutralization. Conclusions: IL-17 is over-expressed in PBMCs of SSc subjects and is related to the higher expression of the pro.-fibrotic cytokines TGFβ, CTGF and PDGF. High concentrations of Vitamin D are able to partially inhibit the expression of these cytokines, supporting the hypothesis that supplementation of Vitamin D in SSc patients could have a potentially mitigating effect on fibrotic processes. References: Yang X et al. Increased frequency of Th17 cells in systemic sclerosis is related to disease activity and collagen overproduction. Arthritis Res Ther. 2014 Jan 7;16(1):R4 Arnson Y et al. Amital H, Serum 25-OH vitamin D concentrations are linked with various clinical aspects in patients with systemic sclerosis: a retrospective cohort study and review of the literature. Autoimmun Rev. 2011 Jun;10(8):490-4 Disclosure of Interest: None declared